2020
DOI: 10.3390/ani10030478
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Nutrient Digestibility, Blood Profiles, Excreta Microbial Counts, Meat Quality and Organ Weight on Broilers Fed with De-Oiled Lecithin Emulsifier

Abstract: This research evaluated the effects of de-oiled lecithin (DOL) as an exogenous emulsifier in broilers. Totally, 480 male broilers (1-d-old, Ross308) were raised for a 35-day feeding experiment. Broilers were randomly divided into three dietary groups including the addition of 0, 61.80%de-oiled lecithin (DOL-60), 97.16%de-oiled lecithin (DOL-97) into the basal diet. Broiler chickens fed with DOL-60 and DOL-97diets had greater body weight gain (BWG) during 1–7 days, 8–21 days, and the overall experimental period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
15
1
Order By: Relevance
“…In this study, the color value of breast meat was increased by lecithin supplementation. Similar results were reported and indicated that the color value of meat also showed a trend in improvement with the increase of emulsifier dosage [ 25 , 27 ]. As the most important textural characteristic of meat, tenderness has great impact on the consumer experience of broiler meat.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, the color value of breast meat was increased by lecithin supplementation. Similar results were reported and indicated that the color value of meat also showed a trend in improvement with the increase of emulsifier dosage [ 25 , 27 ]. As the most important textural characteristic of meat, tenderness has great impact on the consumer experience of broiler meat.…”
Section: Discussionsupporting
confidence: 86%
“…However, most of the studies reported that no significant influences were observed on the N or energy digestibility. Due to the short digestive tract and unstable digestibility of the broilers, the effect of lecithin in increasing the fat digestibility seems not obvious [ 25 ]. That may explain the non-significant effect of lecithin on growth performance or organ weight in broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that quercetin supplementation reduced the increase of adipose tissue weight induced by feeding with a high-fat diet in rats [ 32 , 42 , 43 ]. The content of total cholesterol, LDL-C, HDL-C, and triglyceride in serum are key indicators of lipid metabolism [ 38 , 44 , 45 ]. In this study, the concentrations of serum total cholesterol, LDL-C, HDL-C, and triglyceride were not affected by QS supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial stage of growth and development, due to the digestive system imperfect development of poultry, the secretion of bile and digestive enzymes is insufficient, making the lipid substances in the feed not be fully digested and absorbed (9)(10)(11)(12). The emulsification function of hydroxylated lecithin and soy lecithin contributes to lipid digestion and absorption, and it was found that soy lecithin can improve the utilization of animal oil in feed for poultry (13,14). Both hydroxylated lecithin and soy lecithin have a fatty flavor and good poultry appetizers (2).…”
Section: Introductionmentioning
confidence: 99%